Infant Feeding Breast versus Formula - Jaber Al-Zwaini, Isam; Rasheed Al-Ani, Zaid; Hurley, Walter (IntechOpen, 2020)
Feeding during the first two years of life is very important for the nutrition and growth of an infant. It has a great effect on early morbidity and mortality and long-term effects on health. Breastfeeding has many benefits for both the infant and mother, whereas formula feeding, although associated with disadvantages and problems, can be life-saving for infants who need it. This book examines many aspects of infant feeding and nutrition with chapters covering such topics as the impact of the first 1000 days of nutrition on child health and development, breastfeeding, factors behind the decision to breastfeed or formula feed, and the relationship between breastfeeding and gut microbiota, among others.